Hemodynamic responses to angiotensin-(1-7) in women in their third trimester of pregnancy. (November 2014) - Yamaleyeva, Liliya M.; Merrill, David C.; Ebert, Thomas J.; Smith, Thomas L.; Mertz, Heather L.; Brosnihan, K. Bridget
<x xml:space="preserve">Abstract</x> Background: To understand the role of Angiotensin-(1-7) (Ang-(1-7)) in vasculature of pregnant women, we compared cardiac output (CO), total peripheral resistance (TPR) and forearm blood flow (FBF) responses to Ang-(1-7) infusion between normotensive pregnant women in their third trimester and healthy age matched non-pregnant women. The responses of skin microcirculation to Ang-(1-7) were tested in preeclamptic, normotensive pregnant and non-pregnant women. Responses to Angiotensin II (Ang II) were also determined. Methods: Non-invasive methods for systemic (bioimpedance and VascuMAP), FBF (venous occlusion strain gauge plethysmography), and skin (laser Doppler) hemodynamics assessments were used. Results: Compared to non-pregnant women, systemic infusion of Ang-(1-7) (2000 pmol/min) resulted in a greater increase in CO (9.4 ± 6.4 versus −3.3 ± 2.1%, n = 9–10) in normotensive pregnant women. Brachial local infusion of Ang-(1-7) had no effect on FBF in either group. In non-pregnant and normotensive pregnant women, local Ang II induced a dose-dependent decrease in FBF and increase in forearm resistance at 50 and 100 pmol/min (p < 0.05 versus corresponding baseline, n = 7–10). Following iontophoretic application of 5 mmol/l dose of Ang-(1-7), the change in skin flow was higher in normotensive pregnant versus preeclamptic women (182.5 ± 93 versus 15.76 ± 19.46%, n = 14–15). Skin flow was lower in normotensive pregnant versus preeclamptic women (−46.5 ± 48.7 versus 108.7 ± 49.1%, n = 14–15) following Ang II infusion at 1.0 pmol/min. Conclusion: In the third trimester of pregnancy, Ang-(1-7) induces alterations in CO and differentially regulates micro- and macro-circulations, depending on the dose. Dysregulation in skin vasculature may contribute to the development of vascular dysfunction and hypertension in preeclampsia.